Teledyne inc. equity research paper: are acquisitions everywhereyoulook - Silva, Sofia De Menezes (2022)
This report includes the valuation of Teledyne Technology Inc. (Ticker: TDY) as of December 2021. It aims to mimic an Equity Report and find a stock price for Teledyne on a 12-month basis, i.e., in Dec 2022., for this Discounted Cash Flow Valuation (DCF) Model and a Trading Multiple Valuation were developed. This report will also specifically address the decomposition of the cost of capital (WACC method); and the forecast of the income statement, balance sheet, and free cash flow in the next ten years. After arriving at a final price, a sensitivity analysis and scenarios analysis were also made. Lastly, a Trading Multiple Valuation was developed to support the DCF model. This report also includes the principal limitations of the DCF model.